Modeling the consequences of an L1 grammar for L2 production: simulations, variation, and predictions - Zhang, Sijia; Tessier, Anne-Michelle (Frontiers in Language Sciences, 2024)
This paper presents a constraint-based grammar of Mandarin low vowel + nasal coda (loVN) sequences -first as acquired by L1 learners, and then as transferred to L2 English. We simulate phonological learning in Harmonic Grammar using a gradual, error-driven GLA learner, drawing on evidence from L1 Mandarin speakers' perceptual data to support our initial state assumptions. We then compare our simulation results with L2 English production (both anecdotal and ultrasound data), as well as evidence from Mandarin loanword phonology. Our results align with multiple patterns in the previous empirical literature, including an asymmetry among surface repairs for VN sequences, and we show how these emerge from our assumptions about both the L1 Mandarin grammar and the grammar's evaluation method (i.e. weighted constraints). We discuss the extent to which these results derive from our somewhat novel analysis of place contrasts in L1 Mandarin, and the variability in loVN outputs that we encode directly into the L1 grammar, which are then transferred to the L2 context. Ultimately we discuss how this type of modeling can make falsifiable predictions about phonological development, in both L1 and L2 contexts.